What Factors Affect the Disclosure of Key Audit Matters? Evidence from Listed Companies in Poland Research in Progress - Katarzyna KOLESNIK (Communications of International Proceedings, 2024)
Aim: Key audit matters (KAMs), based on auditor judgment, are the most significant matters in the audit of financial statements of the current period. This study aims to determine the level of Key Audit Matters (KAMs) reporting in the annual reports of companies listed on the Warsaw Stock Exchange in Poland (WSE) from 2021 to 2023, and examine the factors influencing KAMS reporting. Methodology/approach: Using annual reports from 2021 to 2023, 975 annual reports of 325 audited companies from the WSE will be sampled. Content analysis by word count and checklist will be used to quantify the KAMs reporting, while descriptive analysis and multiple regression will be used to analyze the data. Originality/value: This paper is expected to contribute to the limited literature in KAMs research area in a context of CEE countries, such as Poland, which adopted KAMs’ disclosure in 2018.
Keywords: Key Audit Matters; International Standards on Auditing (ISA 701); CEE Countries; Poland